* Ilmu Sebagai Substansi Esensial Dalam Epistemologi Filsafat Pendidikan Islam: Filsafat Pendidikan Islam - Jusua Barus (Jurnal Penelitian dan Ilmu-Ilmu Keislaman, 2021)
Education is not synonymous with just the process of transferring knowledge,because the target of students is not just cleverness, but also targets broaderdimensions in humans such as attitudes, character, behavior and skills.Nevertheless, science becomes a means for a person to achieve the capacitytowards the formation of these aspects. Therefore, a serious study of science,both conceptually, its functions, values, variety and types, as well as sourcesthat are developed into science are fundamental aspects in formulating thecontent of Islamic education. In this case, Islam offers its own distinctiveconception of science in line with its teleological education and its basicassumptions about the potential aspects of humanity, as objects of educationthat must be developed. The most basic of all is that in Islam knowledge is seenas belonging to Allah. Some of them are given to humans directly through theProphets and some are given the material to be studied and developed byhumans themselves based on reason and experience. In Islamic education, thesetwo types of knowledge must be imparted in a balanced way in order to achievethe formation and development of a complete Islamic self, physically andmentally